In Category of Sets and Relations, It Is Possible to Describe Functions in Purely Category Terms - Kreinovich, Vladik; Ceberio, Martine; Brefort, Quentin (Eurasian Mathematical Journal, 2015)
We prove that in the category of sets and relations, it is possible to describe functions in purely category terms.